Feasibility and acceptability of self-collection of Human Papillomavirus samples for primary cervical cancer screening on the Caribbean Coast of Nicaragua: A mixed-methods study - Mitchell, Emma McKim; Hall, Katherine M.; Doede, Aubrey; Rong, Anneda; McLean Estrada, Michelet; Granera, Orlando Benito; Maldonado, Francisco; Al Kallas, Hala; Bravo-Rodriguez, Cassandra; Forero, Mariana; Pokam Tchuisseu, Yolande; Dillingham, Rebecca A. (Frontiers in Oncology, 2023)
Background: Cervical cancer is the primary cause of cancer death for women in Nicaragua, despite being highly preventable through vaccination against high-risk genotypes of the Human Papillomavirus (hrHPV), screening for hrHPV, and early detection of lesions. Despite technological advances designed to increase access to screening in low resource settings, barriers to increasing population-level screening coverage persist. On the Caribbean Coast of Nicaragua, only 59% of women have received one lifetime screen, compared to 78.6% of eligible women living on the Pacific and in the Interior. In concordance with the WHO’s call for best practices to eliminate cervical cancer, we explored the feasibility and acceptability of self-collection of samples for hrHPV testing on the Caribbean Coast of Nicaragua through a multi-year, bi-national, community-based mixed methods study. Methods: Between 2016 and 2019, focus groups (n=25), key informant interviews (n=12) [phase I] and an environmental scan [phase II] were conducted on the Caribbean Coast of Nicaragua in partnership and collaboration with long-term research partners at the University of Virginia and community-based organizations. In spring 2020, underscreened women on the Caribbean Coast of Nicaragua were recruited and screened for hrHPV, with the choice of clinician collection or self-collection of samples. Results: Over the course of the study, providers and potential patients expressed significant acceptability of self-collection of samples as a strategy to reduce barriers currently contributing to the low rates of screening (phases I and II). Ultimately 99.16% (n=1,767) of women chose to self-collect samples, demonstrating a high level of acceptability of self-collection in this pilot sample (phase III). Similarly, focus groups, key informant interviews, and the environmental scan (phases I and II) of resources indicated critical considerations for feasibility of implementation of both HPV primary screening and subsequently, self-collection of samples. Through phase III, we piloted hrHPV screening (n=1,782), with a 19.25% hrHPV positivity rate. Conclusion: Self-collection of samples for hrHPV testing demonstrated high acceptability and feasibility. Through concerted effort at the local, regional, and national levels, this project supported capacity building in reporting, monitoring, and surveilling cervical cancer screening across the continuum of cervical cancer control.